Indonesian’s Risk Perception Level of COVID-19 Based Media Type and Media Exposure Delivering COVID-19 News in The Early Stage of the COVID-19 Outbreak - Anto, Abdul Haris Fitri; Martiarini, Nuke; Dahriyanto, Luthfi Fathan (International Conference on Sustainable Health Promotion, 2023)
The risk perception data of the Indonesian people at the beginning of the COVID-19 outbreak remains undiscovered. In fact, during that period, regardless of the COVID-19 news appearing all the time in all media, Indonesian behaviour did not show any concern about that highly infectious virus. They continued to express normal activities despite the news being everywhere. It seemed the news exposure was meaningless for them. Therefore, this research aims to determine whether exposure to the media about COVID-19 also defines people’s risk perception toward the COVID-19 virus during the early stage of the pandemic. This study involved three variables: the type of media used to update COVID-19 news (X1), the frequency of exposure to COVID-19 news (X2) and the public’s risk perception of the COVID-19 virus (Y). The 1468 research subjects were Indonesian people who used the media to look out for the development of the pandemic. The data collection tool is the risk perception scale developed by Ropeik (2002). Data was collected online using the Googleform application, which spread to 23 provinces. The study’s results were, first, descriptively, during the early days of the pandemic, the Indonesian people’s risk perception of COVID-19 was already high and evenly distributed in all 23 provinces despite their behaviour. Second, social media is the most widely accessed type of media. However, the types of media used to update COVID-19 news significantly correlate with risk perception. Third, the frequency of exposure to COVID-19 news in the media and the public’s risk perception of the COVID-19 virus are significantly correlated. Meaning that the higher the media exposure, the higher the risk perception of COVID-19 would be - and vice versa. The results will be discussed further.